The contribution of PIP2-type aquaporins to photosynthetic response to increased vapour pressure deficit. (30th April 2021) - Israel, David; Khan, Shanjida; Warren, Charles R; Zwiazek, Janusz J; Robson, T Matthew
Abstract : Plasma membrane aquaporin At PIP2;5 is permeable to CO2 and contributes to mesophyll conductance of CO2 in leaves. Abstract: The roles of different plasma membrane aquaporins (PIPs) in leaf-level gas exchange of Arabidopsis thaliana were examined using knockout mutants. Since multiple Arabidopsis PIPs are implicated in CO2 transport across cell membranes, we focused on identifying the effects of the knockout mutations on photosynthesis, and whether they are mediated through the control of stomatal conductance of water vapour ( g s ), mesophyll conductance of CO2 ( g m ), or both. We grew Arabidopsis plants in low and high humidity environments and found that the contribution of PIPs to g s was larger under low air humidity when the evaporative demand was high, whereas any effect of a lack of PIP function was minimal under higher humidity. The pip2;4 knockout mutant had 44% higher g s than wild-type plants under low humidity, which in turn resulted in an increased net photosynthetic rate ( A net ). We also observed a 23% increase in whole-plant transpiration ( E ) for this knockout mutant. The lack of functional plasma membrane aquaporin AtPIP2;5 did not affect g s or E, but resulted in homeostasis of g m despite changes in humidity, indicating a possible role in regulating CO2 membrane permeability. CO2 transport measurements in yeast expressing At PIP2;5 confirmed that this aquaporin is indeed permeable to CO2 .